2013
DOI: 10.1590/s0102-79722013000300019
|View full text |Cite
|
Sign up to set email alerts
|

A segurança dos modelos internos e o conhecimento emocional nas crianças de idade pré-escolar

Abstract: Resumo O objectivo deste estudo foi verifi car se a segurança das representações mentais da relação de vinculação das crianças se correlaciona com um maior conhecimento das emoções, na idade do pré-escolar. Participaram 176 crianças do distrito de Lisboa, com idades entre os 3 e 5 anos. Utilizou-se a escala contínua de segurança do Attachment Story Completion Task e a adaptação portuguesa do Affect Knowledge Test. Os resultados sugerem que as crianças com modelos internos seguros apresentam um maior conhecimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…So, we could see the difference between J. from the first meeting and J. from that day, as he was a boy who didn't want to exchange words with us, much less hug us spontaneously in gratitude. Secure attachment relationships establish a comprehensive relational context in which interactions facilitate the development of emotional understanding in children, and stand out for their flexibility and willingness to allow the child to express and process their negative emotional experiences (REBELO, 2013).…”
Section: May 13th -Picnicmentioning
confidence: 99%
“…So, we could see the difference between J. from the first meeting and J. from that day, as he was a boy who didn't want to exchange words with us, much less hug us spontaneously in gratitude. Secure attachment relationships establish a comprehensive relational context in which interactions facilitate the development of emotional understanding in children, and stand out for their flexibility and willingness to allow the child to express and process their negative emotional experiences (REBELO, 2013).…”
Section: May 13th -Picnicmentioning
confidence: 99%
“…With these stipulations in mind, our research team has developed several well-validated assessments for aspects of SEC, including direct in-person assessments of emotion knowledge with the Affect Knowledge Test -Shortened (AKT-S) and social problem solving with the Challenging Situations Task (CST). The AKT-S and CST measures have been widely used by researchers around the world (e.g., Leyva, Berrocal, & Nolivos, 2014;Kılıç, Ş., & Aytar, 2016;Rebelo, Verissimo, Machado, & Silva, 2013;Sette, Bassett, Baumgartner, & Denham, 2015;Sheard, Ross, & Cheung, 2013;Upshur, Heyman, & Wenz-Gross, 2017). In fact, one recent meta-analysis found that over a third of all effect sizes in studies of children's emotion socialization were measured with the AKT (Zinsser, Gordon & Jiang, 2019).…”
Section: Sec Assessmentmentioning
confidence: 99%
“…Crianças que obtém modelos internos seguros possuem mais chances de apresentar um maior conhecimento das próprias emoções, contudo, para isto, é preciso que os pais possuam práticas positivas, compartilhando sentimentos, suas causas e consequências, estes condizentes aos princípios da modelagem e da modelação (Martins, 2010). Práticas parentais positivas contribuem para o funcionamento social e emocional das crianças, o que demonstra a importância de os pais e/ou cuidadores engajarem-se em observar e orientar as interações sociais dos filhos, bem como suas expressões emocionais (Rebelo, 2012).…”
Section: Descrição Dos Encontros Realizados Com Os Grupos De Paisunclassified